Midline Anterior Neck Inclusion Cyst in a Pediatric Patient: A Case Report and Literature Review with a Dermatologic Perspective - Noemi Brigenti; Rachele Bardelli; Giovanni Paolino; Elisabetta Danese; Paolo Gisondi; Nicola Zerbinati; Giampiero Girolomoni; Andrea Carugno (Medicina)
Midline Anterior Neck Inclusion Cysts (MANICs) are rare congenital anomalies caused by improper embryonic fusion. These superficial benign lesions typically appear yellowish and cystic without deeper anatomic connections. We describe an 11-month-old boy with a stable, asymptomatic, yellow, elastic cystic lesion on the midline of the anterior neck, measuring 4 mm and present since shortly after birth. Clinical, dermoscopic, and ultrasound evaluations confirmed the diagnosis of MANIC. Over six months of observation, the lesion remained stable without growth, infection, or symptoms. MANICs are benign epidermoid cysts with minimal risk of complications that are often mistaken for thyroglossal duct cysts, dermoid cysts, or other congenital anomalies. Unlike thyroglossal duct cysts, they do not move during swallowing or tongue protrusion. Management is usually conservative, with surgery reserved for symptomatic or cosmetically significant cases. This case highlights the importance of parental reassurance and avoiding unnecessary intervention for asymptomatic lesions. Recognition of MANICs is essential for dermatologists and pediatricians evaluating midline neck lesions. A conservative approach with regular monitoring ensures optimal care while minimizing interventions. Further research may clarify the pathogenesis and long-term outcomes of these rare lesions.